REPRESENTASI PEREMPUAN DALAM MASYARAKAT PATRIAKHAL YANG TERGAMBAR DALAM ANTIGONE KARYA SOPHOCLES - Syam, Essy (Universitas Lancang Kuning, 2013)
People can see that women, like men are represented with various representations; some are good, some are bad. Representation is done for certain purpose. That's why in representation, representative is usually the one who gets advantage and on the other hand, the represented is usually put in disadvantageous position. In the case of Antigone, it is found out that the representaion is ambivalent. In one side, Antigone, as the protagonist is represented with positive representations, but in other side, she is represented with less advantageous representation. It ideologically shows that women are not strong and tough figure no matter how hard she tries to be one.